Invented tradition and the new regionalism. The revival of pastoralism in Ochotnica Górna (Polish Carpathian village) - Nowicka, Ewa (Balcanica Posnaniensia. Acta et studia, 2015)
The article is based on anthropological fieldwork in Ochotnica Górna, a village belonging to Podhale region (southern Poland). The study was focused on the revival of transhumance – the type of pastoralism, characteristic for Valachian villages of the entire range of Carpathians. The transhumance has been destroyed by global economic transformation in Poland. Recently it is revived on the new ideological basis connected with the idea of Carpathian and Valachian regionalism.